A thermodynamics-based damage-plasticity model for bond stress-slip relationship of steel reinforcement embedded in fiber reinforced concrete. (1st February 2019) - Huang, Le; Chi, Yin; Xu, Lihua; Deng, Fangqian
Highlights: Two novel evolution laws for damage variables and hardening plasticity are developed. A function that can predict the reduction of bond strength reasonably is proposed. Only a few identifiable parameters with sound physical meanings are required. Abstract: An appropriate bond stress-slip model is of great significance in accurate prediction of the overall responses of a structure in terms of stiffness, bearing capacity, crack pattern distribution, as well as durability in whole lifecycle. In this paper, a damage-plasticity model within the thermodynamic framework is presented, aiming to simulate the bond behavior of steel reinforcement embedded in a well-confined fiber reinforced concrete. With the motivation to reproduce the bond responses faithfully, two novel evolution laws for internal damage variables and hardening plasticity are developed respectively. Meanwhile, a bond reduction function is also proposed, which is capable of reflecting the degradation law in two directions reasonably during the loading history. The model requires only a few identifiable parameters obtained from simple experiments, and each of the parameters has a clear physical meaning. Subsequently, the model is numerically implemented by means of a backward Euler algorithm, and the output is verified by various experimental results from literature. The comparisons with a satisfactory accuracy firmly testify the feasibility of the proposed approach, which pave the way for further theoretical studies on the structural response of FRC structures.